Differences in water relations and total carbohydrate content between precommercially thinned and unthinned Pinus nigra subsp. pallasiana stands - Ayşe Deligöz; Esra Bayar; Musa Genç; Yasin Karatepe (Journal of Forest Science, 2021)
Variations in seasonal responses in water relations and total carbohydrate content (TCC) in one-yearold shoots from precommercially thinned (PCT) and unthinned Anatolian black pine stands were assessed during three seasons (sampling in May, July and September) in 2015-2017. Three different treatments were established: unthinned control with 4 941 stems.ha-1 and two thinned spacing levels (2-2.5 and 3-3.5 m) where 2 133 stems.ha-1 and 1 093 stems.ha-1 were left, respectively. Differences in osmotic potential at turgor loss point (ΨπTLP) between the thinned and unthinned plots appeared only during a water shortage (September) in the second season, with the thinned stands showing lower ΨπTLP than the unthinned stands. Seasonal variation in terms of ΨπTLP was detected in the 3-3.5 m spacing trees. PCT were effective on osmotic potential at full turgor (Ψπ100), relative water content (RWC), symplastic water at saturated point per dry weight of the shoot and dry weight fraction. In both the thinned and unthinned plots, a gradual decline was observed in RWC from May to September in all three years. Generally, although TCC was found to be higher in the 3-3.5 m spacing, control plots were also high in carbohydrates in some periods. Results reflect the ability of this species to survive in changing environments by PCT during dry periods in the three studied seasons. Although PCT has an effect on water potential components and TCC, it is not clear exactly how effective the PCT density is in osmotic adjustment.